Monitoring prediction errors facilitates cognition in action - Plass, John (J Exp Psychol Gen, 2018)
Cognition in action requires strategic allocation of attention between internal processes and the sensory environment. We hypothesized that this resource allocation could be facilitated by mechanisms that predict sensory results of self-generated actions. Sensory signals conforming to predictions would be safely ignored to facilitate focus on internally generated content, whereas those violating predictions would draw attention for additional scrutiny. During a visual-verbal serial digit-recall task, we varied the temporal relationship between task-irrelevant keypresses and auditory distractors so that the distractors were either temporally coupled or decoupled with keypresses. Consistent with our hypothesis, distractors were more likely to interfere with target maintenance and intrude into working memory when they were decoupled from keypresses, thereby violating action-based sensory predictions. Interference was maximal when sounds preceded keypresses, suggesting that stimuli were most distracting when their timing was inconsistent with expected action-sensation contingencies. In a follow-up experiment, neither auditory nor visual cues to distractor timing produced similar effects, suggesting a unique action-based mechanism. These results suggest that action-based sensory predictions are used to dynamically optimize attentional allocation during cognition in action.